Kajian Penggunaan Air Secara Lestari dalam Kalangan Pelajar Sekolah Menengah: Sustainable Water Usage among Secondary School Students - Mariapan, Uma; Mahat, Hanifah; Nayan, Nasir (GEOGRAFI, 2018)
This study aims to analyze the practice of water usage among form four students of Kinta Utara, Perak. This study selected a quantitative method using questionnaire instrument involving 420 secondary school students. Random sampling is used to select the respondents that are form four students in the district of Kinta Utara, Perak. The data were collected through a questionnaire which focuses on five variables: sustainable knowledge, values, skills, attitudes and practices. Analysis of the study is to investigate the level of sustainable usage of water. Furthermore, inference analysis (Pearson correlation and multiple regressions) is used to examine the relationship and contribution of each variable study. The findings of the descriptive analysis show that the level of sustainable usage of water by students is moderate. The analysis of Pearson’s correlation shows that the four independent variables have weak positive relationships and even weaker with sustainable water usage practices. While the findings of multiple regression analysis show that only the factor of attitudes and skills contribute to sustainable usage of water. This clearly demonstrates that the practice of water utilization by students is still at an unsatisfactory level